1989
DOI: 10.1021/jm00129a025
|View full text |Cite
|
Sign up to set email alerts
|

4-(Phosphonoalkyl)- and 4-(phosphonoalkenyl)-2-piperidinecarboxylic acids: synthesis, activity at N-methyl-D-aspartic acid receptors and anticonvulsant activity

Abstract: A series of 4-(phosphonoalkyl)- and 4-(phosphonoalkenyl)-2-piperidinecarboxylic acids were synthesized, and their biological activity was assessed as competitive ligands for the NMDA receptor, both in vitro by using a receptor binding assay ([3H]CGS 19755 binding) and in vivo by using an NMDA seizure model in mice. The analogues were also evaluated in [3H]AMPA and [3H]kainate binding to assess their affinity for non-NMDA excitatory amino acid receptor subtypes. A number of these analogues show potent and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The presence of a characteristic set of signals in the aromatic region of the 1 H NMR spectra of phosphonates IIa and IIb indicated conservation of the heteroaromatic fragment. According to [11], reduction of structurally related systems with hydrogen in the presence of Pd/C is generally accompanied by hydrogenation of heteroaromatic ring.…”
Section: Ia-icmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a characteristic set of signals in the aromatic region of the 1 H NMR spectra of phosphonates IIa and IIb indicated conservation of the heteroaromatic fragment. According to [11], reduction of structurally related systems with hydrogen in the presence of Pd/C is generally accompanied by hydrogenation of heteroaromatic ring.…”
Section: Ia-icmentioning
confidence: 99%
“…It was also shown that vanadyl 1-arylethylphosphonates are characterized by layered structure which makes them promising for the design of functional materials [10]. There are very scanty published data on 1-hetarylethylphosphonates (see, e.g., [11]), though their synthesis and estimation of their biological activity attract undoubted interest. For instance, among the above noted profens, just tiaprofen [(RS)-2-(5-benzoylthiophen-2-yl)propionic acid] exhibits the highest selectivity in the inhibition of synthesis of prostaglandin F 2α .…”
mentioning
confidence: 99%
“…The progressive change of glutamic acid to D-AP5, 73 to the piperidine analog CGS 19755 74 and fi nally to the tetrahydroisoquinoline PD 134705, 75 led to NMDA recep-tor antagonists. Similarly rigidifi cation into the perhydroquinolines 20 , 21 and 22 76 ( Figure 16.38 ) illustrates another application of the conjunctive approach that led to potent AMPA antagonists.…”
Section: B Glutamate Nmda and Ampa Receptor Antagonistsmentioning
confidence: 99%
“…4), most potent as the (3S,4aR,6S,8aR)-isomer (Scheme 17) [67]. The value of N-heteroaromatic systems as templates for the development of aminocarboxylate arrangements in the context of N-alicycles was illustrated in an approach to (2R,4S)-4-(phosphonomethyl)-2-piperidinecarboxylic acid 84 [68]. A Michaelis-Becker reaction between the sodium salt of diethyl phosphite and 4-picolyl chloride 119 furnished the 4-[(diethoxyphosphinyl)methyl]pyridine scaffold 120 [69], which was activated as the N-oxide 121 (via MCPBA oxidation) to ortho-directed addition of a nitrile function (122) as carboxylate surrogate, employing TMSCN reagent.…”
Section: • Synthesismentioning
confidence: 99%